Poverty and Food Security: Trends Among Socio-religious Groups in India. Issue 3 (December 2016) - Das, Panchanan; Sengupta, Anindita
This article analyses food insecurity, poverty risk and inequality in different castes and religious groups in India by utilizing National Sample Survey Organisation's (NSSO) household-level information between 1999–2000 and 2011–2012. The article provides an assessment of the socio-economic characteristics of food-insecure households of the country, and it finds that the poverty risk estimated on the basis of relative poverty line increased both in rural and urban India between 1999–2000 and 2011–2012. The study finds that the likelihood of incidence of food security for the population increased, irrespective of social and religious groups. Food security was lower in Muslims than in Hindus. The relative degree of food security was significantly less among the tribal people compared to other social groups.